Theorizing the Cooling-Off Provision as an Additional Standard of Investment Protection - Di Bella, Danilo (Utrecht Journal of International and European Law, 2021)
Most of International Investment Agreements (IIAs) contains a cooling-off period provision requiring both parties to an investment dispute to make an attempt to settle their differences amicably within a clear time frame, before initiating arbitration. The cooling-off period is triggered by the notice of dispute sent by the investor to the host-State and can range from several months up to one year. At times arbitral tribunals have considered this provision as an optional procedural requirement, others, as a condition precedent for tribunals’ jurisdiction. In either case, tribunals have exclusively focused on the consequences for the investor, whenever the investor had not complied with this waiting period by filing the arbitration prior to its elapse. However, can the cooling-off provision be construed as a procedural standard of investment protection whenever the Respondent-State does not comply with this provision by refusing to engage in consultations with the investor? This article argues so by examining the function, character and content of this provision and by shifting the focal point of arbitral precedents. Indeed, from the investor’s perspective, this provision may well be a treaty-based procedural standard of investment protection to find a cost-effective and prompt solution to a dispute whose breach may call for redress.